Coexistence of Brooke-Spiegler syndrome with psoriasis vulgaris: case report - Michałowska, Olga; Łukowska, Katarzyna; Kozłowska, Anna (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction. Brooke-Spiegler syndrome is a rare, autosomal dominant disease. It is characterized by appearance of cylindromas, trichoepitheliomas and spiradenomas. Multiple cylindromas most frequently are localized on the scalp (turban tumours). Objective. To present coexistence of Brooke-Spiegler syndrome with psoriasis vulgaris – that determined the mode of psoriasis therapy. Case report . A 59-year-old man was admitted to the hospital due to exacerbation of psoriasis vulgaris. The patient had many tumours on the scalp and nodules around the nose and eyebrows. Histopathological investigation revealed multiple cylindromas and trichoepitheliomas. On the basis of the clinical picture and histopathological investigation, diagnosis of Brooke-Spiegler syndrome was established. Additionally, atypical nevus on the skin of the abdomen was recognised. Psoriatic lesions were treated with systemic acitretin and topical ointments. Conclusions . In the presented case, treatment of psoriasis vulgaris was determined by coexistence of adnexal tumours and atypical nevus.